Social support as a moderator of associations between youths’ perceptions of their social images and self-representations in residential care - Calheiros, M. M. (2020)
This study explored the associations between the perceptions that youth in residential care have about their social images (i.e., their perceptions of how other people in general perceive them) and their self-representations, and the moderating role of social support from residential caregivers and friends in those associations. A sample of 926 youths in residential care, aged between 12 and 25 years old, filled out self-report questionnaires tapping their perceptions of their social images, self-representations, and perceived social support. Results indicated that positive youths’ perceptions of their social images were associated to youth's positive self-representations, and that negative youths’ perceptions of their social images dimensions were associated to youth's negative self-representation dimensions. Results also indicated that support from the main residential caregiver and friends moderated associations between youth's perceptions of their social images and self-representations, functioning as a protective factor. These findings underline the importance of youth's perceptions of their social images and the support from residential caregivers and friends for youth in residential care.